An integrative review on female reproductive Pathophysiology according to Islamic Perspective - Azalan, Maryam Syahidah; Abdul Ghani, Radiah (UNiPSAS Press, 2024)
Islamic medical ethics provides Muslims with a crucial framework that directs their lives in all spheres, including women's health. The intersection of Islamic medical ethics with female reproductive physiology and pathology is of paramount importance in today's diverse world, as it not only informs ethical and moral guidelines but also has practical implications for Muslim women's healthcare. However, how these medical ethics address the intricate matters of female reproductive physiology remains to be studied. A significant gap exists in the literature on how religious beliefs influence understanding of biomedicine. Addressing this gap is crucial to ensure that religious and medical guidelines align, ultimately benefiting the well-being of Muslim women. A thorough search of the literature found the existing body of literature emphasizing the relationship between Islamic medical ethics and female reproductive pathophysiology. The scope, including female and maternal health, highlighting menstruation, contraception, pregnancy, childbirth, and fertility in conjunction with an Islamic viewpoint, was identified and documented. The findings revealed that Islamic medical ethics incorporate principles largely compatible with contemporary scientific understanding of female reproductive pathophysiology. Key themes included the importance of preserving life, protecting the mother's health, and the prohibition of harm, which align well with the modern concept of reproductive health. This study emphasizes the evolving knowledge of the female reproductive system through an Islamic jurisprudence point of view. It also highlights the importance of synchronizing religious and medical guidelines to ensure the well-being of Muslim women. The findings may serve as a foundational platform for future dialogues and collaborations between scholars of Islamic jurisprudence and healthcare professionals. Ultimately, this integration may lead to improved reproductive healthcare practices for Muslim women, rooted in the convergence of religious and medical ethics.